THE URGENCY OF ISLAMIC LAW ENFORCEMENT ON ENVIRONMENTAL PRESERVATION IN PAREPARE CITY - Hannani Hannani (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2020)
This study aims to explain environmental damage in Parepare City with the urgency of implementing Islamic law in Parepare City. The research methodology is field research with a qualitative descriptive approach. The results of this study indicate that the impact of environmental damage can affect changes in seasons and weather that are irregular and difficult to predict, thus becoming a source of various disasters such as earthquakes and floods. The urgency of implementing Islamic law to utilize the universe and the environment in prioritizing safety, happiness, peace and security as the goal of human life, preventing various disasters, Parepare City is no exception.